PELATIHAN PENGGUNAAN APLIKASI TERINTEGRASI SEBAGAI UPAYA PENINGKATAN MUTU PELAPORAN KEUANGAN DI UMM BAKERY - Nur Ocvanny Amir; Yohana Agustina; Harpowo (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat, 2021)
Currently, the human resources at UKM UMM Bakery feel that they are not optimal in implementing financial management. This service aims to train UMM Bakery employees to better understand financial management, know whether this business is profitable or not, and can make accurate and effective financial reports. The results of this service activity are in the form of an integrated financial reporting system in Microsoft Excel 2016. Community Service activities are carried out by several methods, starting with a survey to UMM Bakery, identifying the needs of financial management. The next step is to conduct training in the preparation of financial statements using Microsoft Excel to suit the needs of partners. The final step is to evaluate financial management training activities. As a result of this training, partners can improve their ability to manage finances. Partners can understand and apply a financial reporting system that is precise and simple to apply. This is shown by the partners' ability to apply the integrated financial reporting system.